2009
DOI: 10.1080/13682820802008820
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in people with severe aphasia

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Keywords: health-related quality of life; aphasia; proxy ratings; stroke outcome. Permanent 2 AbstractBackground: Health-related quality of life (HRQL) measures are increasingly used to help us understand

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 25 publications
1
75
1
2
Order By: Relevance
“…As people with stroke and PD experiencing communication difficulties and mood problems tend to have reduced QOL [91], it is perhaps surprising that CST participants have higher self-rated QOL than a large international sample of other people with disabilities. This is consistent with large-scale studies involving healthy adult members of international choirs, who also reported higher scores on the WHOQOL-BREF than the norm [43].…”
Section: Qol In Group Singingmentioning
confidence: 99%
“…As people with stroke and PD experiencing communication difficulties and mood problems tend to have reduced QOL [91], it is perhaps surprising that CST participants have higher self-rated QOL than a large international sample of other people with disabilities. This is consistent with large-scale studies involving healthy adult members of international choirs, who also reported higher scores on the WHOQOL-BREF than the norm [43].…”
Section: Qol In Group Singingmentioning
confidence: 99%
“…For example, aphasia severely affects people's social and emotional well-being (Hilari and Byng, 2009). The focus group of PWA suggested meeting informally as a solution to social isolation.…”
Section: What Information Do People With Stroke Want To See On the Wementioning
confidence: 99%
“…In this study, aphasia is the focus, with a view to contribute to expand the knowledge in this area, due to the scarcity of studies, mainly in the literature about Speech-Language Pathology, and also due to its importance in several aspects in the life of individuals, for example, the dependence on a caretaker for daily activities, the disruption of social relations, language impairment, psycho-affective changes, such as depression, isolation, among others (1)(2)(3)(4) .…”
Section: Introductionmentioning
confidence: 99%
“…This condition can result in a negative impact on the person's life, since, besides affecting language, it may interfere in the related processes as practical life, social, affective, interactive, and interpretative relations (1,3,4) . Thus, it is of the almost importance to investigate the aspects of aphasics QOL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation